Barnadråp - Brottets varande eller icke varande i den moderna svenska strafflagstiftningen - Alqvist,Axel (2023)
The provision regarding infanticide in Swedish law is, in many ways, a distinct provision compared to other offenses in the Swedish Penal Code. Several Swedish legal compilations have regulated this offense for hundreds of years, ranging from the 1734 Act to the current Swedish Penal Code. Due to the infrequent application of the offense, lack of legal precedent, the historical and traditional impressions associated with the offense, and the wording of the paragraph distinguishing between different types of victims, reflections have arisen regarding the existence or non-existence of this offense in modern Swedish criminal law. These reflections became particularly apparent following the publication of an investigative report in 2014. The research's main question and, likewise, the purpose of this thesis precisely address whether infanticide can be considered redundant and whether there might be a need to abolish the current criminal provision. Furthermore, it examines whether there is a need to replace the current provision with a new one. The thesis also questions the offense's connection to crimes based on tradition and how infanticide relates to the principle of equality before the law. The problem formulations arising from the main questions are addressed in the dissertation, then elevated to a discussion in the analysis, and finally presented in multiple conclusions. In this way, the main purpose of the thesis is realized: an examination of the current law, supported by the legal doctrinal method. The examination approaches the research subject through a critical legal perspective. Consequently, the existing law can be questioned and problematized, considering both arguments for and against the factors pertaining to the position of infanticide in Swedish criminal law. However, the analysis in the thesis expresses strong arguments suggesting that infanticide as an offense cannot be considered redundant. Therefore, it cannot be deemed necessary to either abolish the current provision or introduce a new one. This assessment is made in consideration of multiple circumstances, leading to a clearly stated and substantiated conclusion.
Keywords: straffrätt; barnadråp; traditionsbrott; likhet inför lagen; infanticide